Clinical phenotypes within nonconvulsive status epilepticus. (9th July 2021) - Lattanzi, Simona; Giovannini, Giada; Brigo, Francesco; Orlandi, Niccolò; Trinka, Eugen; Meletti, Stefano
Abstract: The study aimed to identify distinct phenotypes within nonconvulsive status epilepticus (NCSE). Consecutive episodes of NCSE in patients at least 14 years old were included. The level of consciousness was assessed through the Glasgow Coma Scale (GCS). Etiology of NCSE was defined as symptomatic (acute, remote, progressive) or unknown. Electroencephalographic (EEG) recordings were searched for lateralized periodic discharges (LPDs), generalized sharply and/or triphasic periodic potentials (GPDs), and spontaneous burst suppression (BS). According to treatment response, NCSE was classified as responsive, refractory, or superrefractory. Average linkage hierarchical cluster analysis was performed with Pearson correlation as similarity measure. Two hundred twenty‐nine episodes of NCSE were included. Three clusters were identified. The first cluster linked GCS score 3–8, presence of spontaneous BS on EEG, acute symptomatic etiology, and treatment superrefractoriness. The second cluster gathered GCS score 9–12, presence of LPDs or GPDs on EEG, unknown etiology, and treatment refractoriness. The third cluster associated GCS score 13–15, absence of LPDs, GPDs, and spontaneous BS on EEG, and progressive and remote symptomatic etiology with treatment responsiveness. Phenotyping the heterogeneity of NCSE into electroclinical clusters can contribute to understanding correlations between pathologic and clinical domains, assessing the intrinsic severity of NCSE episodes, and estimating the likelihood of treatment responsiveness.